INTUITION: a data platform to integrate human epilepsy clinical care and support for discovery - Maharathi, Biswajit; Mir, Fozia; Hosur, Karthik; Loeb, Jeffrey A. (Frontiers in Digital Health, 2023)
In order to make appropriate clinical decisions, clinicians take into account many types of data from multiple sources, to synthesize a diagnosis and plan. However, current health systems have siloed data, making it challenging to develop information platforms that mimic this process into a single place for comprehensive clinical evaluation and research. INTUITION is a human brain integrative data system that facilitates multimodal data integration, unified storage, cohort selection, and analysis of multidisciplinary datasets. Here we describe the use of INTUITION to include electronic health records together with co-registered neuroimaging and EEG from patients who undergo invasive brain surgery for epilepsy. In addition to providing clinically useful visualizations and analytics to help guide surgical planning, INTUIITON also links a bank of human brain epileptic tissues from specific brain locations to quantitative EEG, imaging, histology, and omics studies in a unique, completely integrated informatics platform. Having a clinically useful platform for multimodal dataset integration can not only aid clinical management decisions, but linked to spatially mapped tissue samples, creates a unique resource for research and discovery.